2022
DOI: 10.3389/fonc.2022.958720
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming resistance to immune checkpoint inhibitors in hepatocellular carcinoma: Challenges and opportunities

Abstract: Hepatocellular carcinoma is one of the leading causes of cancer mortality globally, and its incidence is increasing. Immune checkpoint therapy has revolutionized the treatment of hepatocellular carcinoma over the past few years. However, only a limited proportion of patients with hepatocellular carcinoma respond to immunotherapy. Despite the significant breakthroughs, the molecular mechanisms that drive immune responses and evasion are largely unresolved. Predicting tumor response and resistance to immune chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…To gain deeper insight into the potential mechanisms behind the antitumor immune response induced by Ru1105 in combination with 808 nm laser in mice, we analyzed the immune cells from the vaccinated mice by flow cytometry. The existence of cytotoxic T cells (CTLs, CD8 + T cells) within tumors serves as a distinctive indicator of specific immune responses, correlating with a favorable prognosis across various cancer types. Additionally, inducers of ICD ultimately prompt a T cell-mediated immune response, involving the activation of CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…To gain deeper insight into the potential mechanisms behind the antitumor immune response induced by Ru1105 in combination with 808 nm laser in mice, we analyzed the immune cells from the vaccinated mice by flow cytometry. The existence of cytotoxic T cells (CTLs, CD8 + T cells) within tumors serves as a distinctive indicator of specific immune responses, correlating with a favorable prognosis across various cancer types. Additionally, inducers of ICD ultimately prompt a T cell-mediated immune response, involving the activation of CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] Approximately 40% of HCC patients show constitutive activation of Wnt/β-catenin signaling induced by mutations in related genes. 25 Studies using HCC mouse models have confirmed that activation of Wnt/β-catenin signaling obstructed DCs recruitment, thereby promoting immune escape and resistance to PD-1 treatment. 26 Sequencing data from HCC patients treated with ICIs suggested that patients without Wnt/β-catenin mutations respond to ICIs treatment, thus providing empirical evidence for the correlation between ICIs resistance and Wnt/β-catenin mutations.…”
Section: Mutation Of Pathwaysmentioning
confidence: 99%
“…Exosomes are expected to serve as key vehicles for MTB pathogen-associated molecular patterns (PAMPs), through which MTB s inhibit host immune responses, and promote immune escape and survival. The dynamic change and balancing tendency of cytokines is a manifestation of immune effect in many immune-related diseases ( 40 43 ). MTB conjugated to toll-like receptor 2 (TLR2) triggers mast cells to release exosomes containing high levels of chemokine (C-C motif) ligand 2 (CCL2), IL-4, and IL-13, and causes macrophage M2 polarization, which potentiates the immune escape effect of MTB ( 44 ).…”
Section: The Roles and Mechanisms Of Exosomes In Tbmentioning
confidence: 99%